Pengaruh Pemberian Contract Relax Stretching Terhadap Pengurangan Tingkat Nyeri Otot Upper Trapezius Pada Siswa Jurusan Teknik Komputer Jaringan (Tkj) Di Smk Kasatrian Solo - Fajarirawati, Adesty Nanda; , Arif Pristianto, SSt.FT.,M.Fis (2017)
Background: Contract relax stretching is one technique of Proprioceptive Neuromuscular Facilitation (PNF) method that combines the isometric contraction and passive stretching which aims to reduce pain, improve flexibility, and improve Range of Motion (ROM). Objective: The purpose of this study was to investigate the effects of contract relax stretching on reduction upper trapezius muscle pain level for students department of Computer Network Engineering (CNE) in Kasatrian Solo Vocational High School. Method: This research uses a Quasi Experimental approach , of the technique used is the pre test and post test with control group design. The total sample in this study as 28 samples were then devided into two groups, namely the experiment group was given contract relax stretching and the control group was given static stretching. This study carried out for 4 weeks with every day exercise frequency. Techniques of analysis data using the Paired Sample t-Test and Independent Sample t-Test. Result: Based on statistical result obtained by value p = 0,026 in the experiment group, which means there is the effects of contract relax stretching on reduction upper trapezius muscle pain. While in the control group was obtained value of p = 0,826, which means there is no effects of static stretching on reduction upper trapezius muscle pain. The effects of different test between two group obtained by value p = 0,000, which means there is the different effects between the experiment group and control group. Conclusion: Giving of contract relax stretching evident to give the effects on reduction upper trapezius muscle pain. Key Word: Proprioceptive Neuromuscular Facilitation (PNF), contract relax stretching, muscle pain, upper trapezius.